The Impact of Cognitive-Behavioral Therapy on Enhancing Self-Control and Reducing Anger among Individuals Recovered from COVID-19 - Khanjani Veshki, Sahar; molaei yasavoli, Mehdi; Saghebi, Parisa (Journal of Assessment and Research in Applied Counseling (JARAC), 2025)
Abstract Objective: The COVID-19 pandemic not only poses physical health challenges but also has significant psychological implications. This study aimed to examine the effectiveness of cognitive-behavioral therapy (CBT) in enhancing self-control and reducing anger among individuals recovered from COVID-19. Method: A quasi-experimental design with pre-test, post-test, and follow-up assessments and a control group was used. The study population included individuals diagnosed with COVID-19 who sought treatment at [MASKED FOR REVIEW], Iran. A total of 30 participants were selected through convenient sampling and randomly assigned to either an experimental group (n = 15) or a control group (n = 15). The experimental group received nine sessions of CBT, while the control group received no intervention. Data were collected using Tanji’s (1999) Self-Control Questionnaire and Buss and Perry’s (1992) Aggression Questionnaire. Data analysis was conducted using analysis of covariance (ANCOVA) and repeated measures ANOVA to evaluate treatment sustainability. Findings: The results indicated that CBT significantly improved self-control and reduced anger among individuals recovered from COVID-19. Conclusion: CBT appears to be an effective intervention for enhancing self-control and reducing anger in individuals who have recovered from COVID-19.